2001
DOI: 10.1111/j.1750-3639.2001.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Galectins Are Differentially Expressed in Supratentorial Pilocytic Astrocytomas, Astrocytomas, Anaplastic Astrocytomas and Glioblastomas, and Significantly Modulate Tumor Astrocyte Migration

Abstract: Galectins, a family of mammalian lectins with specificity to ␤-galactosides, are involved in growthregulatory mechanisms and cell adhesion. A relationship is assumed to exist between the levels of expression of galectins and the level of malignancy in human gliomas. A comparative study of this aspect in the same series of clinical samples is required to prove this hypothesis. Using computerassisted microscopy, we quantitatively characterized by immunohistochemistry the levels of expression of galectins-1, -3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 55 publications
6
109
0
2
Order By: Relevance
“…We previously reported [5] that galectin-3 expression increases during glioma progression, whereas other studies have found a global decrease in expression [7,14]. This discrepancy may be due to the specific regions of tumors analyzed, as higher galectin-3 expression is associated with the invasive regions in vivo.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…We previously reported [5] that galectin-3 expression increases during glioma progression, whereas other studies have found a global decrease in expression [7,14]. This discrepancy may be due to the specific regions of tumors analyzed, as higher galectin-3 expression is associated with the invasive regions in vivo.…”
Section: Discussionmentioning
confidence: 41%
“…This discrepancy may be due to the specific regions of tumors analyzed, as higher galectin-3 expression is associated with the invasive regions in vivo. Indeed, glioblastoma cells demonstrated greater motility on galectin-3 in vitro, suggesting that increased galectin-3 promotes invasion [7]. In addition, galectin-3 expression is not restricted to the tumor cells.…”
Section: Discussionmentioning
confidence: 95%
“…18 The specificity of the galectin-3 antibody was checked by immunoblotting and ELISA assays with controls to exclude any crossreactivity to other galectins (especially galectin-1, which is abundant in human lungs), as previously detailed. [18][19][20]33 An internal positive control consisted in the expression of galectin-3 (also labeled Mac-2) by alveolar macrophages. The negative control sections were immunostained under the same conditions, but with the omission of the primary antibody.…”
Section: Galectin-3 Expression In Lung Carcinomasmentioning
confidence: 99%
“…15,16 Galectins are involved in cell growth, apoptosis and cell migration features. [17][18][19][20] Of these 14 galectins, galectin-3, a chimera-type galectin, is of special interest since its structure harbors a sugar-combining site, a collagensensitive stalk and a short N-terminated section, acting as a target for phosphorylation. 21 What is particularly intriguing about this sole chimera-type galectin is its presence in nuclear, cytoplasmic and extracellular sites, 22 its ability to interact with a variety of carbohydrate and protein ligands and to form pentamers with unique crosslinking abilities, 23 its strong antiapoptotic activity coupled with the nuclear export of the phosphorylated form (for example in chemotherapeutic treatment), 24 and its effect on promoter activity of cyclin D1, 25 which is a prognostic marker in the adenocarcinoma subgroup of lung carcinomas.…”
mentioning
confidence: 99%
“…12 It acts as a physiological modulator of cellular adhesion and growth and may be involved in neoplastic transformation. [13][14][15] Like galectin-3, galectin-8 is approximately 80% homologous in amino acid sequence between human and mouse. 11 The expression of galectin-3 has recently emerged as a potential diagnostic marker of some cancers.…”
mentioning
confidence: 99%